2016
DOI: 10.5897/jpp2015.0368
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical screening of methanolic dried galls extract of Quercus infectoria using gas chromatography-mass spectrometry (GC-MS) and Fourier transform-infrared (FT-IR)

Abstract: The main objective of this study was to determine the phytochemical composition from the dried galls of Quercus infectoria, using methanolic extraction and report the main functional components by using infrared (IR) technique. The phytochemical compound screened by gas chromatography-mass spectrometry (GC-MS) method. Twelve bioactive phytochemical compounds were identified in the methanolic extract of Q. infectoria. The identification of phytochemical compounds is based on the peak area, retention time molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…A total of seven components were found to be the common for both extracts of QL. Previous studies on Quercus genus suggested that the species are rich in monounsaturated fatty acids, mostly oleic acid and also essential fatty acids such as linoleic (ω-6) and linolenic (ω-3) fatty acids, sesquiterpenes, terpenoids, flavonoids and phenolic acid [20,21,26] and in the present study same pattern of phytoconstituents were observed in the leaves and bark extracts of QL. Differences in quantity and quality of chemical components of any plant extract are highly influenced by several genetic and environmental factors, such as the genetic and seasonal variation, geographical origin, and the part of the plant used for the study, even agronomic conditions, developmental stage, time of collection, extraction method and solvent system [27].…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…A total of seven components were found to be the common for both extracts of QL. Previous studies on Quercus genus suggested that the species are rich in monounsaturated fatty acids, mostly oleic acid and also essential fatty acids such as linoleic (ω-6) and linolenic (ω-3) fatty acids, sesquiterpenes, terpenoids, flavonoids and phenolic acid [20,21,26] and in the present study same pattern of phytoconstituents were observed in the leaves and bark extracts of QL. Differences in quantity and quality of chemical components of any plant extract are highly influenced by several genetic and environmental factors, such as the genetic and seasonal variation, geographical origin, and the part of the plant used for the study, even agronomic conditions, developmental stage, time of collection, extraction method and solvent system [27].…”
Section: Resultssupporting
confidence: 84%
“…The yield of bark and leaves extracts were found to be 9.7% and 13.6%, respectively. A range of volatile phytoconstituents have been identified by GC-MS in different Quercus species other than QL [20,21]. In the present study, the percentages (area per cent) and the retention time (RT) of the components are listed in Tables 1 and 2 Linoleic acid is an omega-6-fatty acid and is enormously used in cosmetic industries, whereas the conjugated linoleic acid was accounted to have anticarcinogenic, fat reducing, antiatherogenic and immune enhancing activity [22].…”
Section: Resultsmentioning
confidence: 99%
“…Q .rubra all extracts were better as a result of Imipenem against all bacteria against P. aeruginosa and K. pneumoniae respectively, In general, the methanol solvent is better than the n-hexan, because it contains many active plant compounds compared to n-hexane (Ameera et al, 2016) and in particular the methanol extract has a greater effect against P. aeruginosa and S. aureus, while the n-hexane extract has the greatest effect against bacteria K. pneumonia. These results indicate that Q. rubra have better antibacterial activity for burn patients than antibiotics, so, it is recommended that making an ointment from these plants may be bene icial for treatment.…”
Section: Compare Extracts At Concentration 400 Mg / ML With Imipenem Antibioticmentioning
confidence: 89%
“…linucheae compared to all other species tested. 3-trifluoroacetoxypentadecane has previously been shown to have antimicrobial properties 56 , however, far more work is needed to accurately define the function of these halogenated compounds in Symbiodiniaceae.…”
Section: Discussionmentioning
confidence: 99%